COMPARISON OF THE CLINICAL OUTCOMES OF HYPERGLYCEMIC CRISIS IN COVID-POSITIVE AND COVID-NEGATIVE PATIENTS: A RETROSPECTIVE COHORT STUDY - Cadeliña , Jekrylei; Fontanilla, Joy Arabelle (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Since the start of the COVID-19 pandemic, there has been an increased incidence of hyperglycemic crisis in hospitals, involving both those with and without COVID-19 infection. Our objective was to compare the clinical outcomes between COVID-positive and COVID-negative patients who were admitted for hyperglycemic crisis from March 2020 to February 2022. METHODOLOGY We conducted a retrospective cohort study of adult patients with hyperglycemic crisis on admission from March 1, 2020 to February 28, 2022 at the St. Luke’s Medical Center - Global City. They were divided into two groups: those with and without COVID-19 infection. Their medical records were reviewed to determine and compare their clinical background, presenting clinical manifestations, non-COVID acute conditions, biochemical and clinical parameters, treatment regimen, and clinical outcomes. Descriptive statistics were employed. RESULTS The COVID-positive group had significantly higher in- hospital mortality rate prior to resolution of hyperglycemic crisis (p=0.008) and had a significantly higher proportion of patients who developed acute respiratory failure (p=0.000) and multi-organ failure (p=0.003). They were also significantly older and had a significantly higher proportion of patients who had preexisting malignancy, presented with cough and dyspnea, and received concurrent steroid treatment. The COVID-negative group significantly had more patients who presented with abdominal pain, had urinary tract infection on admission, and developed acute kidney injury. CONCLUSION Patients hospitalized with hyperglycemic crisis who also had COVID-19 infection had higher in-hospital mortality rate before resolution of hyperglycemic crisis, compared to those who did not have COVID-19 infection.